Mititoxic properties of Cucurma longa against a major contributor of oral mite anaphylaxis, the grain mite Suidasia pontifica - Mangoba, Mark Anthony Angeles (Animo Repository, 2020)
Current investigation aims to evaluate the mititoxic properties of turmeric crude extract (TCE) against Suidasia pontifica–a source of human allergens and major contributor of oral mite anaphylaxis (OMA) or pancake syndrome. Based on the response of S. pontifica, the estimated minimum effective concentration (MEC) of TCE to achieve complete mortality was 2.25–2.50 g/L. Twenty-three chemical components were identified in TCE based on GC-MS analysis. The four major compounds were as follows: aR-tumerone (50.63%), curlone (15.42%), α-curcumene (6.48%), and 3-octanol (5.88%). The TCE was relatively superior in terms of toxicity and volume concentration to control the population of S. pontifica. Further, it can be used as a complement or potential replacement to conventional synthetic acaricides on the market. © 2020 Informa UK Limited, trading as Taylor & Francis Group.